2018
DOI: 10.1111/ap.12221
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Psychological wellbeing in a Sample of Australian Actors

Abstract: Objective:The objective of the current study was to explore what factors might impact the psychological wellbeing of adult, Australian professional actors. Method: Twenty South Australian actors were recruited using purposive and snowball sampling. Ten were male and 10 female, ranging in age from 22 to 66 years old, with self-reported professional experience ranging from 1 to 50 years. The participants were interviewed indepth about their experiences of being an actor, with a particular focus on wellbeing, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 42 publications
(55 reference statements)
0
29
0
Order By: Relevance
“…Studies contextualised their research within a variety of conceptual frameworks, most frequently aligning with well-being ( n = 4) or occupational stress ( n = 3). Within those studies drawing on well-being frameworks, Robb et al (2018) used a eudaimonic conceptualisation of well-being (Ryff, 2014), Ascenso and Perkins (2013) drew on Seligman's PERMA framework (Seligman, 2011), and Quested et al (2013) aligned with both self-determination theory (Deci and Ryan, 1985, 2000) and basic needs theory (Deci and Ryan, 2000). Of those studies aligned with the occupational literature, a variety of concepts were considered.…”
Section: Summary Of Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies contextualised their research within a variety of conceptual frameworks, most frequently aligning with well-being ( n = 4) or occupational stress ( n = 3). Within those studies drawing on well-being frameworks, Robb et al (2018) used a eudaimonic conceptualisation of well-being (Ryff, 2014), Ascenso and Perkins (2013) drew on Seligman's PERMA framework (Seligman, 2011), and Quested et al (2013) aligned with both self-determination theory (Deci and Ryan, 1985, 2000) and basic needs theory (Deci and Ryan, 2000). Of those studies aligned with the occupational literature, a variety of concepts were considered.…”
Section: Summary Of Studiesmentioning
confidence: 99%
“…However, jazz musicians and those working in freelance settings discussed opportunities to input into creative and management decisions as positive contributors to well-being (Cooper and Wills, 1989; Dobson, 2010b). Performing artists reflected on the importance of social support for their well-being, identifying the positive benefits of working alongside individuals with a shared interest (Smith, 1989; Robb et al, 2018).…”
Section: Summary Of Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…A study with a cohort of 800 actors found that they are more affected by depression than the mean population (Maxwell et al, 2015). Some qualitative accounts attribute at least part of this effect to fictional experiences of violence, with actors reporting posttraumatic stress disorder (PTSD)-like symptoms in connection to their work, particularly with the repeated embodiment of scenarios involving rape, physical violence, grief, and suicide (Robb et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The distinctness of empathy-based strain constructs is unclear as well as the constructs' use in varying professions. In our review of the literature, samples ranging from more traditional caregiving professions such as social workers, therapists, chaplains, and nurses, to more unexpected secondhand trauma-exposed workers such as actors (Robb et al 2016), qualitative research transcriptionists (Kiyimba and O'Reilly 2016), criminal lawyers (Vrklevsiki and Franklin 2008), and sports coaches (Day et al 2013), were represented. Moreover, individuals who were exposed to (secondary) trauma through narratives were included, in addition to individuals exposed to (primary) trauma in violent work contexts (e.g., in "enforcement" professions; Kita 2015) and in nonhuman contexts (e.g., animal care; Rank et al 2009).…”
Section: To Which Contexts and Professions Is Empathy-based Stress Apmentioning
confidence: 99%